Function and evolution of the long noncoding RNA circuitry orchestrating X‐chromosome inactivation in mammals. (13th May 2016) - Furlan, Giulia; Rougeulle, Claire
Abstract : X‐chromosome inactivation (XCI) is a chromosome‐wide regulatory process that ensures dosage compensation for X‐linked genes in Theria. XCI is established during early embryogenesis and is developmentally regulated. Different XCI strategies exist in mammalian infraclasses and the regulation of this process varies also among closely related species. In Eutheria, initiation of XCI is orchestrated by a cis ‐acting locus, the X‐inactivation center ( Xic ), which is particularly enriched in genes producing long noncoding RNAs (lncRNAs). Among these, Xist generates a master transcript that coats and propagates along the future inactive X‐chromosome in cis, establishing X‐chromosome wide transcriptional repression through interaction with several protein partners. Other lncRNAs also participate to the regulation of X‐inactivation but the extent to which their function has been maintained in evolution is still poorly understood. In Metatheria, Xist is not conserved, but another, evolutionary independent lncRNA with similar properties, Rsx, has been identified, suggesting that lncRNA‐mediated XCI represents an evolutionary advantage. Here, we review current knowledge on the interplay of X chromosome‐encoded lncRNAs in ensuring proper establishment and maintenance of chromosome‐wide silencing, and discuss the evolutionary implications of the emergence of species‐specific lncRNAs in the control of XCI within Theria. WIREs RNA 2016, 7:702–722. doi: 10.1002/wrna.1359 This article is categorized under: Regulatory RNAs/RNAi/Riboswitches > Regulatory RNAs RNA in Disease and Development > RNA in Development